1996
DOI: 10.1128/aac.40.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ciprofloxacin in pediatric cystic fibrosis patients

Abstract: The pharmacokinetic characteristics of ciprofloxacin were studied in 10 children with cystic fibrosis, aged from 6 to 16 years, who had completed the standard regimen of intravenous ceftazidime and amikacin. The aim of the investigation was to derive dosing guidelines for young cystic fibrosis patients to be treated with ciprofloxacin. Each child received ciprofloxacin given as two 30-min infusions (10 mg/kg of body weight each) 12 h apart; this was followed by the administration of oral ciprofloxacin (15 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…This range is lower than the values averaging ∼8.4 mg/L reported by Schaefer et al . 18 following intravenous doses of 10 mg/kg to paediatric patients with cystic fibrosis, but is consistent, when corrected for dose, with their range of ∼2.5–5 mg/L (mean 3.5 mg/L) achieved with an oral dose of 15 mg/kg. In contrast, despite using a higher dose of 15 mg/kg, Peltola et al 19 observed similar values of C max (0.5–5.3 mg/L) when they administered ground tablets in water and mean C max values of ∼2–2.7 mg/L following an oral suspension of 10 mg/kg.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This range is lower than the values averaging ∼8.4 mg/L reported by Schaefer et al . 18 following intravenous doses of 10 mg/kg to paediatric patients with cystic fibrosis, but is consistent, when corrected for dose, with their range of ∼2.5–5 mg/L (mean 3.5 mg/L) achieved with an oral dose of 15 mg/kg. In contrast, despite using a higher dose of 15 mg/kg, Peltola et al 19 observed similar values of C max (0.5–5.3 mg/L) when they administered ground tablets in water and mean C max values of ∼2–2.7 mg/L following an oral suspension of 10 mg/kg.…”
Section: Discussionsupporting
confidence: 55%
“…Studies following the intravenous administration of ciprofloxacin have identified a biexponential decline with a short distribution half-life of ∼10–30 min, 1618,35,36 but the sparse sampling schedule in the present study precluded the identification of a distribution phase. The population model indicated a rapid absorption of ciprofloxacin with an estimated half-life of 14 min after a lag of ∼45 min.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In particular, it has been suggested that daily doses must be at least 30 mg/(kg·day) intravenously or 40 mg/(kg·day) orally. 18,19 …”
Section: Clinical Pharmacologymentioning
confidence: 99%
“…The spiked plasma samples were thoroughly mixed by vortexing and allowed to equilibrate for 12 h at 4°C. After equilibration, protein free plasma was obtained by carrying out ultra filtration (Millipore Centrifree ® filtration units) by centrifugation of 0.5 ml of plasma at 2000g for 20 min (Schaefer et al, 1996, Murthy et al, 2005). The amount of unbound drug present in the filtrate was measured by HPLC after suitable dilution with PBS.…”
Section: Methodsmentioning
confidence: 99%